Comparison of Decompression, Decompression Plus Fusion, and Decompression Plus Stabilization for Degenerative Spondylolisthesis: A Prospective, Randomized Study. Issue 7 (August 2018) - Inose, Hiroyuki; Kato, Tsuyoshi; Yuasa, Masato; Yamada, Tsuyoshi; Maehara, Hidetsugu; Hirai, Takashi; Yoshii, Toshitaka; Kawabata, Shigenori; Okawa, Atsushi
Abstract : Study Design: This is a prospective, randomized controlled trial. Objective: To prospectively assess the long-term clinical results of decompression alone, decompression plus fusion, and decompression plus stabilization for degenerative spondylolisthesis. Summary of Background Data: Symptoms of lumbar spinal stenosis due to degenerative spondylolisthesis originate from compression of the dural sac or nerve root. Essentially, this condition is treated by performing a decompression of neural structures. Posterolateral lumbar fusion and posterior pedicle-based dynamic stabilization are additional techniques performed to ensure improved prognosis. However, to date, the selection of a surgical procedure for lumbar spinal stenosis due to degenerative spondylolisthesis remains debatable, especially in terms of the addition of instrumentation because of the few available prospective, randomized studies. Materials and Methods: We randomly assigned patients who had 1 level lumbar spinal stenosis due to degenerative spondylolisthesis at the L4/5 level to undergo either decompression alone (decompression group), decompression plus fusion (fusion group), or decompression plus stabilization (stabilization group). Outcomes were assessed using the Japanese Orthopaedic Association and Visual Analogue Scale scores. Results: In total, 85 patients underwent randomization. The follow-up rate at 5 years was 86.4%. The fusion and stabilization groups showed higher blood loss and a longer operative time than the decompression group. The fusion group showed longer postoperative hospital stay than the decompression group. In terms of clinical outcomes, all scores significantly improved postoperatively, and these outcomes were maintained at 5 years postoperatively in each group. There were no significant differences among the groups at 1 and 5 years postoperatively. Conclusions: Additional instrumentation operation for low-grade (<30%) degenerative spondylolisthesis did not result in superior results to decompression alone at 1 and 5 years postoperatively. Level of Evidence: Level II.